Impact of COVID-19 pandemic on the care of severe burns in Japan: Repeated survey of specialized burn care facilities. Issue 4 (June 2023) - Kiyozumi, Tetsuro; Saitoh, Daizoh; Ogura, Takayuki; Morino, Kazuma; Takeda, Taichi; Narumi, Atsushi; Hashimoto, Ichiro; Sasaki, Junichi; Sakurai, Hiroyuki
Abstract: Background: The spread of coronavirus disease 2019 (COVID-19), which began in 2020, has had a major impact on healthcare systems. The spread of COVID-19 has been reported to have affected the readiness to treat patients with burns worldwide. However, the existing reports have evaluated burn care status within a limited time period during the pandemic, and no report clarifies the change in the impact of infection status on burn care from the beginning of the pandemic to the present. Methods: Japanese Society for Burn Injuries–accredited burn care facilities were surveyed using questionnaires on April 9–23, 2020; June 23–July 6, 2020; July 9–21, 2021; and January 21–31, 2022. Differences between groups were evaluated using Friedman's test or Bonferroni's multiple comparison test, as appropriate. Results: From the 103 facilities included in the study, we received 85, 55, 56, and 58 responses in the first, second, third, and fourth surveys, respectively. We could continuously observe 34 facilities. The rate of acceptance of patients with severe burns improved significantly over time (P < 0.05). However, in the second and third surveys, there was an increase in the number of respondents who did not accept patients with burns irrespective of COVID-19 status. Conclusions: The number of facilities treating patients with burns who have COVID-19 is increasing; however, COVID-19 care may negatively impact routine burn care. It is necessary to continuously examine medical resource allocation through methods such as information sharing by academic societies. Highlights: We surveyed the effect of coronavirus disease 2019 (COVID-19) on burn care. An increasing number of facilities can treat patients with COVID-19 who have burns. Some facilities changed their decision to accept patients with severe burns. Information should be shared to prepare for the reallocation of medical resources.